Sebum Components Dampen the Efficacy of Skin Disinfectants against Cutibacterium acnes Biofilms - Dilini Kumaran; Sandra Ramirez-Arcos (Microorganisms, 2024)
At Canadian Blood Services, despite the use of 2% chlorhexidine and 70% isopropyl alcohol (standard disinfectant, SD) prior to venipuncture, Cutibacterium acnes evades eradication and is a major contaminant of platelet concentrates (PCs). Since C. acnes forms bacterial aggregates known as biofilms in the sebaceous niches of the skin, this study aimed to assess whether sebum-like components impact disinfectant efficacy against C. acnes leading to its dominance as a PC contaminant. C. acnes mono-species and dual-species biofilms (C. acness and a transfusion-relevant Staphylococcus aureus isolate) were formed in the presence and absence of sebum-like components and exposed to SD, a hypochlorous acid-based disinfectant (Clinisept+, CP), or a combination of both disinfectants to assess disinfectant efficacy. Our data indicate that sebum-like components significantly reduce the disinfectant efficacy of all disinfectant strategies tested against C. acnes in both biofilm models. Furthermore, though none of the disinfectants led to bacterial eradication, the susceptibility of C. acnes to disinfectants was heightened in an isolate-dependent manner when grown in the presence of S. aureus. The reduction of skin disinfection efficacy in the presence of sebum may contribute to the overrepresentation of C. acnes as a PC contaminant and highlights the need for improved disinfection strategies.